KUALITAS PEWARNAAN KAYU SENGON (PARASERIANTHES FALCATARIA (L). NIELSEN) DENGAN MENGGUNAKAN EKSTRAK KULIT BUAH MANGGIS, KULIT KAYU AKASIA DAN KULIT KAYU BAKAU - Welly, Rodius; Wardenaar, Evy; Mariani, Yeni (JURNAL HUTAN LESTARI, 2016)
The usage of wood is not limited to household appliances but also used wood for the exterior. Wood have a high decorative value because of its color and fiber pattern. Wood decorative value increase the economic value of wood. Sengon (Paraserianthes Falcataria (L). Nielsen), one of wood species which not have interesting pattern and color thus through this research dyeing process conducted to know the optimum concentration of Sengon staining by using several natural extract such as the rind of Mangstosteen fruit (Garcinia mangostana L.), bark of Acacia mangium and Mangrove tree bark. There were four level of concentration used 5%, 10% , 15% and 20%. The result showed that the highest extract yield percentage derived from A. mangium bark followed by mangrove bark and mangoosten fruit rind (32.67%, 29.09% and 28.37 respectively). While for pH value, mangoosteen fruit rind extract have the highest value followed by mangove bark extract and A. Mangium bark (5.8-6, 5-7 and 5-5.2 respectively). The highest absorbance value derived from A. Mangium bark extract followed by mangosteen fruit rind extract and mangrove bark extract (0.715 ppm, 0.476 ppm and 0.439 ppm respectively). A. Mangium bark extract also shown the highest absorbance followed by mangrove bark extract and mangosteen fruit rind (0.699 ppm, 0.477 ppm and 0.4 ppm) in 478 nm wavelength with 800C. Dyeing process with mangosteen fruit rind extract with 20% concentration resulted highest retention value (9.064 kg/m3) while for the brightness resulted from 10% concentration. Kaywords: A.mangium, Mangrove bark and Mangosteen fruit rind, Natural dye, Sengon.